AD, Volume 1, n° 2, 1976 - Full Issue - BUJRA, Abdalla S. (Africa Development, 1976)
Contents Abdalla S. Bujra Editorial Note ...................... iv ARTICLES Jeremy Swift Desertification and Man in the Sahel ...................... 1 Mahamadou Maïga The Policy of Rice Import Substitution: The Case of the Senegal River Valley and Delta ............... 9 Rumman Faruqi & Peter O'Brien Foreign Technology in the Growth of the Modern Manufacturing sector in Ethiopia 1950- 1970 ............... 23 Abdul Aziz Jalloh Regional Integration in Africa: Lessons from the Past and Prospects for the Future ..................... 44 Samir Amin After Nairobi: an Appraisal of UNCTAD IV ....................... 58 Tony Moody Peasant Agriculture, Commercial Production and Employment in Kenya ............................ 62 FOCUS ON RESEARCH INSTITUTES ISSER, Legon, Ghana Institute of Statistical, Social and Economic Research .................. 73 CREDILA, Dakar, Senegal Centre de Recherche, d'Etude et de Documentation sur les Institutions et les Legislations Africaines ................. 77